Distinction between Planned and Unplanned Readmissions following Discharge from a Department of Internal Medicine - Kossovsky, M. P.; Sarasin, F. P.; Bolla, F.; Gaspoz, J.-M.; Borst, F. (Methods of Information in Medicine, 1999)
Readmission rate is often used as an indicator for the quality of care. However, only unplanned readmissions may have a link with substandard quality of care. We compared two databases of the Geneva University Hospitals to determine which information is needed to distinguish planned from unplanned readmissions. All patients readmitted within 42 days after a first stay in the wards of the Department of Internal Medicine were identified. One of the databases contained encoded information needed to compute DRGs. The other database consisted of full-text discharge reports, addressed to the referring physician. Encoded reports allowed the classification of 64% of the readmissions, whereas full-text reports could classify 97% of the readmissions (p <0.001). The concordance between encoded reports and full-text reports was fair (kappa = 0.40). We conclude that encoded reports alone are not sufficient to distinguish planned from unplanned readmissions and that the automation of detailed clinical databases seems promising.
Keywords: Health Services Research; Patient Data Collection; Readmissions; Hospital Information Systems